Forschungsjournal Soziale Bewegungen (De Gruyter Oldenbourg, 2011)
The research journal is devoted to issues of democratization, social science research on social movements, and political sociology. To better serve as an indicator, seismograph, and driver for social processes, the journal operates at the intersection between research on social movements, social practice, politics, and the everyday world. Its focus is on the interdisciplinary exploration of the "soft side" of institutional change in societies.